1991
DOI: 10.1021/ja00013a014
|View full text |Cite
|
Sign up to set email alerts
|

Extreme environmental sensitivity of the rate of intramolecular electron transfer in mixed-valence 1',1'''-dibenzylbiferrocenium triiodide

Abstract: The extreme sensitivity of the rate of intramolecular electron transfer for the mixed-valence 1',1"'-dibenzylbiferrocenium cation to different environments is explored. Two different crystalline morphologies of 1',1"'-dibenzylbiferronium triiodide (1) could be identified by their different crystal habits (needle and plate-like crystals). They are structurally characterized by single-crystal and powder X-ray diffraction techniques. The single-crystal X-ray structure of a parallelepiped (needle) crystal of 1 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
24
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 1 publication
9
24
0
Order By: Relevance
“…The change in the solubility of the iodide PIL in acetone after the treatment of I 2 indicated that triiodide-based PILs were successfully synthesized, which was further identified by elemental analysis (Table S2). As reported, triiodide anions exist in an isolation state in solutions because they are electronically more stable instead of I 2 -Ipair in solvents, [37,38] we believe that the delocalized negative charge in triiodide vs iodide leads to weakened interaction of anions with hydrogens in the 1,2,4-triazolium heterocycle ring, which eventually results in shielding of those acidic protons. The boiling point of iodine is 184 o C, close to the observed decomposition temperature, at which iodine leaves the system and drives the equilibrium to the decomposition side.…”
Section: Resultssupporting
confidence: 51%
“…The change in the solubility of the iodide PIL in acetone after the treatment of I 2 indicated that triiodide-based PILs were successfully synthesized, which was further identified by elemental analysis (Table S2). As reported, triiodide anions exist in an isolation state in solutions because they are electronically more stable instead of I 2 -Ipair in solvents, [37,38] we believe that the delocalized negative charge in triiodide vs iodide leads to weakened interaction of anions with hydrogens in the 1,2,4-triazolium heterocycle ring, which eventually results in shielding of those acidic protons. The boiling point of iodine is 184 o C, close to the observed decomposition temperature, at which iodine leaves the system and drives the equilibrium to the decomposition side.…”
Section: Resultssupporting
confidence: 51%
“…[75] Many years ago, a similar behavior was also reported by Hendrickson for the 1',1'''-dibenzylbiferrocenium triiodide monocation. [76][77][78][79] Indeed, a polycrystalline sample can be regarded as a solid solution containing population of various conformers of the same molecules. In the case of complex p-1(PF 6 ) the relative conformation of the bridging ligand and the metal centers switches the magnitude of the electronic coupling between the metal centers yielding population of trapped and detrapped mixed-valence species at the spectroscopic time scale.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The influence of grinding sample on physical properties has been well studied for spin crossover transitions [27]. In the case of mixed-valenced biferrocenium salts, Hendrickson found a reduction of the electron-transfer rate in mixed-valence 1?,1 §-dibenzylbiferrocenium triiodide (3p, n 0/1) as a result of mechanical grinding [21]. A change in valence for a transition-metal complex is generally accompanied by the coordination sphere reorganization.…”
Section: Fe Mo ¨Ssbauer Characteristicsmentioning
confidence: 99%
“…In the case of a binuclear mixed-valence biferrocenium cation, the value of g tensor anisotropy (Dg0/g jj (/g Þ ) can be used as a rough estimate of the nature of the electronic ground state of the cation. Here, we are interested in studying the influence of grinding on the electronic ground state by EPR technique [21].…”
Section: Electron Paramagnetic Resonancementioning
confidence: 99%
See 1 more Smart Citation